Analysis of the Management of the Museum Pusaka Nias in Cultural Conservation, Biodiversity, and Sustainable Herbal Knowledge - Zebua, Anna Mariana; Bayu Wijayanto; Siti Fatimah; Eka Asih Febriani; Rosdianto (Sumatra Journal of Disaster, Geography and Geography Education, 2026)
This research aims to analyze the management of the Museum Pusaka Nias in the sustainable conservation of culture, biodiversity, and herbal knowledge. The research methodology used is a descriptive qualitative approach with data analysis using SWOT. The results of the analysis show that the main strengths of the Museum Pusaka Nias lie in its collection of authentic, high-value artifacts, cultural legitimacy, indigenous community networks, and education and conservation of various endemic biodiversity owned by the Nias community. The weaknesses of the Museum Pusaka Nias include ticket prices/donations for tourists from outside the region and limited digital infrastructure that is not yet adequate. For opportunities, the Museum Pusaka Nias has considerable opportunities including increasing cultural tourism trends, academic and government partnerships. Meanwhile, threats lie in tectonic natural disasters, coastal abrasion/degradation of coastal ecosystems and degradation of physical collections. As a solution to overcome these, the Museum Pusaka Nias must be able to adapt to current developments such as technological improvements, the development of thematic tour packages, disaster preparedness and collection risk management, multi-stakeholder partnerships and strengthening human resource capacity.